Handling Stress in Hospitalized Patients: Integration of Islamic Counseling and Dhikr - Farmawati, Cintami; Mutohharoh, Annisa; Idris, Saleha (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Inpatients can experience stress due to various factors, including the disease they suffer from and the unfamiliar hospital environment. The stress experienced by patients can affect their physical and mental health and have an impact on the recovery process. One effective strategy to overcome stress experienced by patients is by integrating Islamic counseling and dhikr. This study aims to find out how Islamic counseling and dhikr affect stress in hospitalized patients. This study is a qualitative study. The subjects in the study were three hospitalized patients who were experiencing stress. Data collection techniques used interviews, observation, and documentation. Data analysis used was data reduction, data presentation, and drawing conclusions. The results of the study showed that the integration of Islamic counseling and dhikr can handle stress in hospitalized patients. The study found a significant difference in the stress levels of hospitalized patients before and after they implemented Islamic counseling and dhikr. The integration of Islamic counseling and dhikr, or what is often called dhikr relaxation, can provide benefits and help patients to overcome stress problems. The integration of counseling and dhikr is the right combination; both can provide a more holistic and meaningful solution for patients in dealing with stress. It is recommended that future researchers expand their research by conducting quantitative studies on their effectiveness.